ON THE ORIGINS OF THE PROFESSION: THE INSTITUTIONALIZATION OF RAINING OF COSTA RICAN SOCIAL WORK (1942-1952) - Brenes Rodríguez, Milton Ariel (2015)
In this article, the author reconstructs and describes the process of institutionalizing of training of Costa Rican Social Work profession during the historical period of 1942 to 1952. For this purpose, considering the contextual basis that allowed such professionalization, various aspects are taken up in the analysis, such as party trends, faculty, administrative oscillations, curriculum and foundations of the School of Social Work, including in its constitution, semi-private, and its entry to the University of Costa Rica.